Pemanfaatan Kecerdasan Buatan (AI) dalam Pembelajaran Personalisasi - Nadatul Paujiyah; Alya Shaffira Adistya (PT. Willy Print Art, 2025)
In today's digital era, the use of artificial intelligence (AI) is increasingly developing in education, especially to support personalized learning. This study aims to explore the use of AI in adjusting the learning process to the needs, styles, and learning speed of students. This study applies a qualitative method with a literature review approach, which analyzes various literature and the latest research results. The results of the study show that AI helps adjust learning materials based on individual characteristics, accelerates feedback to students, increases learning motivation, and creates a more adaptive and interactive learning experience. However, challenges such as student data privacy and gaps in technology access are still major obstacles in the application of AI in education. Nevertheless, AI has great potential as a foundation for the development of future learning applications that are more inclusive and responsive to student needs. This research is expected to contribute to enriching educational technology studies and become a reference for educators and learning application developers in integrating AI effectively and ethically.